FoxM1 Promotes Cell Proliferation, Invasion, and Stem Cell Properties in Nasopharyngeal Carcinoma - Luo, Weiren; Gao, Fei; Li, Siyi; Liu, Lei (Frontiers in Oncology, 2018)
Background The self-renewal and tumourigenicity of FoxM1 in nasopharyngeal carcinoma (NPC) remain largely unknown. In this study, we attempt to investigate the self-renewal and tumourigenicity of FoxM1 and its clinical significance in nasopharyngeal carcinoma (NPC). Methods Several assays including cell counting Kit-8 (CCK-8) assays, colony formation, flow cytometry, immunofluorescence, tumor spheres and mice model were used to detect the biological function of FoxM1 in NPC. The association between FoxM1 and clincalpathological features, and stem cell markers was analyzed using immunohistochemistry. Results High expression of FoxM1 was prominently present in the T4 stages, cancer cells migrating into the stroma and vasculature. Overexpression of FoxM1 enhanced tumor proliferation, cell cycle progression, migration and stress fibers formation in vitro. In NPC tissues, FoxM1 correlated significantly with stem cells-related clincalpathological features including late clinical stage, tumor recurrence and distant metastasis. Meanwhile, FoxM1 linked closely with the expression levels of stem cell markers including Nanog, Sox2 and OCT4 in tumor samples, and also promoted the expression of these stemness-related genes in vitro. Moreover, FoxM1 conferred the self-renewal properties of cancer cells by increasing side populations (SP) cells and formed larger and more tumor spheres. Importantly, FoxM1 enhanced the ability of tumourigenicity of NPC cell lines in mice xenograft. Conclusions We demonstrate that FoxM1 greatly induces cancer progression and cancer stem cell features in NPC.